Doppler echocardiography: validity of a quantitative analysis of velocity curves - COLONNA, G.; DIEBOLD, B.; TOUATI, R.; BLANCHARD, D.; PERONNEAU, P.; GUERMONPREZ, J. L.; MAURICE, P. (Archives of Acoustics, 1984)
The clinical evaluation of the Doppler diagnosis was performed at the level of inferior vena cava for quantification of tricuspid insufficiency (TI) and in the aortic arch for evaluation of aortic insufficiency (AI). The ratios were calculated between systolic and diastolic components: 1. for AI, between peak systolic and end diastolic components, 2. for TI between peak systolic and peak diastolic components. The results showed that: 1. the compliance of the vessels may prevent the propagation of moderate modifications of velocity curves; 2. associated valvular stenosis may disturb curves even far down-stream; 3. systolodiastolic variations of vessel diameter may modify the relationship between angiographic grades and ratios: 0.890 for TI (61 patients) and 0.86 for pure AI (65 patients); for both lesions, the differences between the groups, defined according to the angiographic grade, were significant.